Knowledge and attitude related to medical ethics among medical students - S., Iswarya; S., Bhuvaneshwari (International Journal Of Community Medicine And Public Health, 2018)
Background: There has been growing public awareness regarding the ethical conduct of medical practitioners, and complaints against physicians appear to be escalating. After completing their studies, healthcare professionals are expected to know ethical principles and apply them in their clinical practice. Hence, this study was conducted to assess the knowledge and attitude of medical ethics among final year medical students. Methods: Cross sectional study was conducted among final year Medical students in a private medical college. After obtaining permission from Institutional ethics committee, the purpose of the study and nature of information which has to be furnished from the students was explained to them. Willingness to participate in the study was obtained from participants using written consent form. Data was collected among 135 medical students using pre tested self-administered questionnaire. The respondents were asked to grade their responses on a 3 point Likert scale. Results: Study results showed majority 87% of students felt patient wishes must always be adhered to. In contrast 65% of students felt doctors must do what is best irrespective of patient’s opinion. About 64.7% of them disagreed consent is required only in case of operations and not for tests and medications. Nearly half (47%) of the students were of opinion privacy of the patient must not be ignored for benefit of larger group. Conclusions: The fact that many respondents had neutral opinion to some questions may indicate their lack of awareness or knowledge in that area and their inability to decide. Hence there should be sufficient training classes, workshops, conferences to stress the importance of ethical practice.